Brain serotonin depletion enhances the sodium appetite induced by sodium depletion or beta-adrenergic stimulation - Lima,Hawlinston R. C. (2004)
We investigate the influence of brain serotonin depletion on the sodium appetite. Rats depleted of serotonin through the systemic administration of p-chlorophenylalanine (300 mg/kg, ip, for 2 days) showed an intense natriorexigenic response induced by sodium depletion (furosemide, 20 mg/kg, sc, 24 h before water and 1.8% NaCl presentation). Intake of 1.8% NaCl was always higher than that observed for the control group (12.9 ± 1.4 and 21.4 ± 3.0 mL vs 5.7 ± 1.2 and 12.7 ± 1.6 mL, 30 and 300 min after water and saline presentation). After 24 h, the natriorexigenic response continued to be significantly higher compared to control (33.6±5.1 vs 21.9±3.6 mL,P <0.05). Fourteen days after p-chlorophenylalanine administration, 1.8% NaCl intake did not differ from controls. Serotonin-depleted rats expressed an early natriorexigenic response after isoproterenol administration on the third day after the first injection of p-chlorophenylalanine. An increase in 1.8% NaCl intake was first observed at 120 min (1.9 ± 0.2 vs 0.45 ± 0.3 mL,P <0.05) and remained high up to the end of the 24-h observation period (17.3±3.2 vs 1.1±0.5 mL,P <0.05). After 7 and 14 days, the natriorexigenic response became comparable to that of control animals. Present results show that brain serotonin depletion exaggerates the sodium appetite induced by the paradigm of sodium depletion or after beta-adrenergic stimulation.